Disproporations and Development of Regional Insurance Markets and Managing Them - V. G. Khalin; G. V. Chernova; E. L. Prokopjeva (Управленческое консультирование, 2020)
The current stage of development of the Russian insurance market in most regions is accompanied by imbalances in its development — a mismatch between the level of development of the regional insurance market and the needs of the region for insurance protection, as well as large deviations of insurance indicators at the regional level from their reference values, for example, the best or average across the insurance market countries. Therefore, the study of the causes of such imbalances, as well as the development of managerial decisions to reduce and eliminate them, is extremely relevant. The article contains an analysis of imbalances in the development of regional insurance markets and their respective regions, as well as a list of measures to reduce them. It also contains an analysis and assessment of imbalances in the development of regional insurance markets (RIM) due to deviations in the real quality and cost of services provided by the region from the reference ones. Particular attention is paid to identifying regional risks that determine the types of insurance that are priority for the region in question. The study used the method of experimental comparative analysis, deduction and statistical methods. The proposed approach to identifying imbalances in the development of RIM and the formation of managerial decisions to reduce them can be used to increase the effectiveness of the functioning of RIM, assessed by the two proposed criteria. The results of the work can be used to develop and implement national and regional strategies for socio-economic development, including the use of insurance as an institution of social and financial protection against risks.